Erwinia phage Asesino is a nucleus-forming phage that lacks PhuZ - Amy Prichard; Annika Sy; Justin Meyer; Elizabeth Villa; Joe Pogliano (Scientific Reports)
Abstract As nucleus-forming phages become better characterized, understanding their unifying similarities and unique differences will help us understand how they occupy varied niches and infect diverse hosts. All identified nucleus-forming phages fall within the Chimalliviridae family and share a core genome of 68 unique genes including chimallin, the major nuclear shell protein. A well-studied but non-essential protein encoded by many nucleus-forming phages is PhuZ, a tubulin homolog which aids in capsid migration, nucleus rotation, and nucleus positioning. One clade that represents 24% of all currently known chimalliviruses lacks a PhuZ homolog. Here we show that Erwinia phage Asesino, one member of this PhuZ-less clade, shares a common overall replication mechanism with other characterized nucleus-forming phages despite lacking PhuZ. We show that Asesino replicates via a phage nucleus that encloses phage DNA and partitions proteins in the nuclear compartment and cytoplasm in a manner similar to previously characterized nucleus-forming phages. Consistent with a lack of PhuZ, however, we did not observe active positioning or rotation of the phage nucleus within infected cells. These data show that some nucleus-forming phages have evolved to replicate efficiently without PhuZ, providing an example of a unique variation in the nucleus-based replication pathway.